Implementing the Independent Learning Curriculum on Student Learning Motivation in Fashoin Dependent Classes - Rika Riwayani; Hamidah Suryani; Nur Wulan (Universitas Pendidikan Ganesha, 2024)
In the world of education, the curriculum has an important role in determining the direction and quality of learning experienced by students. The implementation of an independent learning curriculum designed to increase student involvement and responsibility in the learning process. This research is ex-post facto research with a quantitative type of research. This research aims to determine the description of the implementation of the Independent Learning Curriculum in the Fashion Department and the Learning Motivation of Students in the Fashion Department. This type of research is ex-po facto. The population in this study were class X and XI students majoring in fashion design. The sampling technique uses a population sample method where if the population is less than 100 then the entire population becomes the sample, namely a sample size of 50 students. The data collection techniques used are observation, documentation and questionnaires. The analysis techniques used are descriptive statistical analysis and inferential analysis. The results of the research show a picture of the implementation of the independent learning curriculum majoring in fashion design with a percentage of 34% or 17 students who produced an interval of 40-43 which was categorized as moderate; and Description of the learning motivation of students majoring in fashion design with a percentage of 32% or 16 students who produced the highest interval of 43-46 which was in the high category. If the implementation of an independent learning curriculum is proven to be effective in increasing motivation, the implication for the world of education is that there will be a push to implement a more flexible and adaptive approach in various practice-oriented classes.